Initiating activation in diabetes self-management from patients’ perspective - Syahnaz Mohd Hashim; Idayu Badilla Idris; Nasrin J; Rafidah B; Shalisah Sharip (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Patients’ active role is crucial in managing chronic illnesses like type 2 diabetes. Current evidence demonstrated patients who were activated had better clinical outcomes. Some factors influencing patient activation have been identified but there is little knowledge on how patients successfully start to take their role in managing diabetes. This study aimed to explore how patients begin to activate themselves in self-management. The narrative inquiry was taken as the qualitative methodological approach. Ten participants with type 2 diabetes were purposively sampled from a public primary care clinic in Malaysia. In-depth interviews were conducted and recorded. The data were analysed with thematic analysis. Three themes and four subthemes were generated. The first theme, “Learning what to do” describes the learning process from social networks and healthcare professionals that helped to define their role. The second theme highlighted that patients wished for a gradual approach in initiating activation, i.e. “Taking one step at a time”. They started with a more straightforward self-management task and needed more time to take up their role. The third theme pointed out that when patients could not perform certain self-management tasks, they would engage with someone else to help: “Engaging with someone for challenging tasks.” In conclusion, diabetes self-management education is substantial in developing ‘patient activation,’ i.e. patient’s ability to self-manage. The self-management plan should also be realistic and suit patients’ circumstances. Having a health partner or buddy among family members or peers is helpful when trying to adopt good dietary habits and perform regular exercise.